Mutilation, deception, and sex changes. Issue 2 (June 1987) - Lavin, M
Abstract : The paper considers and rejects two arguments against the performance of sexual reassignment surgery. First, it is argued that the operation is not mutilating, but functionally enabling. Second, it is argued that the operation is not objectionably deceptive, since, if there is such a thing as our 'real sex', we do not know (ordinarily) what it is. The paper is also intended to shed light on what our sexual identity is and on what matters in sexual relations.